PENGARUH PRAKTIK KEBERLANJUTAN SOSIAL RANTAI PASOKAN TERHADAP KINERJA RANTAI PASOKAN YANG DIMEDIASI OLEH KINERJA PEMASOK DAN OPERASIONAL PADA USAHA MIKRO DAN KECIL DI KOTA BANDA ACEH - Humaira Durunnafis; Muhammad Adam (Departemen Manajemen, 2021)
Abstract: The purpose of this study is to measure the effect of supply chain social sustainability towards performance supply chain mediated by supplier and operational performances. Micro and small manufacturing enterprises within Banda Aceh city are used as population. It consists approximately 2.871 businesses in Banda Aceh, but only 351 are taken as samples. The sampling technique uses Probability Sampling and the type of sampling is Proportionate Stratified Random Sampling. Data was collected through survey using questionnaire. The Structural Equation Modeling is used on analytical method to determine the effect of variables involved. The result shows that operational performance plays major role on social sustainability of supply chain towards performance supply chain while supplier performance has no effect at all on micro and small enterprises in Banda Aceh.